Terrorism and International Humanitarian Law (IHL): Defining the Status of Islamic State of Iraq and Syria (ISIS) - Bashar, Zahirul (Asian Journal of International Affairs, 2021)
The wings of terror of ISIS has started since 2014. By 2019, ISIS the terrorist organization, spreading its wings over Syria, Iraq, and many other states around the world causing the death of thousands. The suffering due to acts of terrorism is innumerable. The conflict in Syria has reached a threshold that triggered the application of the Geneva Conventions and its Additional Protocols. ISIS is violating the International Humanitarian Law in every phase of its operation. Though ISIS is not a party to the aforesaid Conventions, the rules of IHL apply to it. This paper has envisaged the conflict in the Syrian Arab Republic and the classification of the armed conflicts. In addition, it has shown the origin of ISIS and their terrorist attacks during the last five years and how the parties in the conflicts including ISIS have responsibilities under the IHL. In doing so, the paper has relied on existing scholarly articles, books, newspaper reports as well as other international instruments.